Emotional experiences of a head teacher during the first two year period of leadership in a secondary school in Cyprus - Mourettou, Mary (2017)
This case study explored the nature of emotional experiences of a female newly appointed head teacher, the Novice, in a public Cypriot lower secondary school in Cyprus. Coping strategies and the development of interpersonal relationships with teachers, in association with trustworthy leadership, were followed in terms of a step by step process. The study draws upon qualitative research methods, rooted within the naturalistic paradigm in order to illuminate the emotions associated with the professional and organizational socialization of the Novice in the context of Cyprus. Data were collected through head teacher observation and semi- structured interviews, as well as semi-structured interviews and questionnaires with teachers.